PELAKSANAANuPERALIHAN HAKuATAS TANAHu BERDASARKAN HIBAHuWASIAT OLEHuPELAKSANA WASIAT BERDASARKAN PERATURANuPEMERINTAH NOMORu24 TAHUNu1997 - Awal Candra Pamungkas; Djauhari Djauhari (Jurnal Akta, 2017)
Research on "Implementation of Land Rights Transition Based on Grants by Testament E ecuti es Based on Go ernment Regulation Number 24 Year 1997" aims to know: (1) How are the legal grounds for registration and transfer of ownership of land based on the grant of wills, (2) registration and transfer of ownership of land based on a grant of probate in Kendal District, (3) How practices, constraints and solutions in the transfer of land rights are based on a grant of probate in Kendal Regency.This research uses empirical juridical approach, empirical juridical approach in this research means that in analyzing the problem is done by combining legal materials (which is secondary data) with primary data obtained in the field.The results of this study indicate as follows: (1) Fundamentally the concept of grants and testaments in the re iew of the  i il  ode defines grants and testaments solely as a ci ic relationship, while in khasanah study of Islamic Law interpreted as piety and ma'ruf. Thus, the concept of grants and testaments is  ery applicable when applied in the community of Kendal Regency, which is predominantly Muslim, (2) Land registration process in the Land Office of Kendal Regency has been done and in accordance with the procedures and requirements mandated in Go ernment Regulation No. 24 Year 1997 on Land Registry. Therefore, the purpose of land registration as intended in Article 3 PP No.24 of 1997 can be realized, (3) The implementation of registration of land rights in the district of kendal in relation to grants and wills goes well, starting from registration in PPAT to Office Land. Factors that hamper the registration process seem to be difficult because of misinformation, objections or objections from other parties, and brokering practices in the management of land registration that is still rife.Keywords: Grants, Testament, Registration and Transfer of Rights, Land Rights